Deteksi Produksi Toksin Stx-1 dan Stx-2 dari Escherichia coli O157:H7 Isolat Lokal Hasil Isolasi Feses dan Daging Sapi - Suardana, I Wayan; Krisna Erawan, I Gusti Made; Sumiarto, Bambang; Widaya Lukman, Denny (Jurnal Veteriner; Vol 10 No 4 (2009), 2009)
Shiga toxin produced by Escherichia coli O157:H7 can cause outbreaks and sporadic cases of serious human diseases. The diseases are indicated by hemorrhagic colitis and hemolytic uremic syndrome. Meat and meat products have been identified as vehicles of food borne disease caused by E.coli O157:H7. The main aim of this research was to identify the correlation between the level of E.coli O157:H7 contamination and the presence of Shiga toxin (Stx1 and Stx2) by applying method of Vero toxin Escherichia coli-Reverse Passive Agglutination Test (VTEC-RPLA). The results showed that 3 of 7 isolates and 1 of 4 isolates isolated from feces of cattle and beef, respectively produced Stx 1 (VT1). In the detection of Stx 2 (VT2), 4 of 7 isolates and 1 of 4 isolates, isolated from the same samples were found to produce this toxin. According to all isolates, in this research showed, 1 isolate was found to produce VT2, 4 isolates to produce both VT1 and VT2, while 6 isolates showed negative results either to VT1 or VT2.
Keywords: E.coli O157:H7, VT1, VT2